ANALYSIS OF THE IMPLEMENTATION OF THE EDUCATIONAL QUALITY ASSURANCE SYSTEM AT STATE VOCATIONAL SCHOOL 3 KEMARITIMAN BIAK NUMFOR - Yoas Yafdas; Zulkifli; Tubagus Pamungkas (RADJA PUBLIKA, 2025)
The quality management system is an approach in realizing a quality assurance program that is very important to be placed as scientific studies in the context of measuring and predicting the readiness of educational institutions. The purpose of this study is to determine the planning for implementing the SPMP implementation in order to improve the quality of schools at SMK Negeri 3 Kemaritiman Biak Numfor., Garut Regency. This research was conducted using a qualitative approach. The method used is descriptive analysis. Techniques and research instruments using observation, interviews and documentation. While the analysis technique is done through data reduction, data display and drawing conclusions. The results of the study indicate that quality planning is carried out in several steps, namely quality mapping through school self-evaluation (EDS) activities, which are followed by preparation of compliance plans, implementation of education quality, evaluation of education quality and standard setting so that it can describe school quality accurately. Implementation of education quality assurance that has been planned to fulfill eight National Education Standards.